Pengaruh Dana Pihak Ketiga, Non Performing Financing, dan Kecukupan Modal Terhadap Profitabilitas Pada Bank Umum Syariah Tahun 2018-2021 - Dicgy Diandra Aishya; Dewi Sartika Nasution; Riduan Mas'ud (Jurnal Perbankan Syariah, 2022)
The purpose of this study was to determine the effect of third party funds, non-performing financing and capital adequacy on profitability at Islamic commercial banks for the 2018-2021 period. The research method used is a quantitative correlation approach. the technique of collecting funds is by using a random sampling technique in the form of financial reports at the Financial Services Authority (OJK). data analysis technique with multiple linear regression with Eviews 10 analysis tool. Based on the estimated data, it is found that the Third Party Fund (DPK) variable has no significant effect on the profitability of Islamic commercial banks with a significance level of 0.7315 > 0.05, and the non-performing financing (NPF) variable has no significant effect on profitability with a significance level of 0, 3253 > 0.05. While the variable capital adequacy / Capital Adequacy Ratio has a significant effect on profitability with a significance level of 0.0117 <0.05.